Path dependence of accountants: Why are they not involved in corporate sustainability? - Julius Wenzig; Anne-Katrin Nuzum; Stefan Schaltegger (Business Strategy and the Environment, 2022)
Accounting has been identified as a key area to inform managers seeking to transform businesses towards sustainability. Empirical research, however, shows that management accountants are scarcely involved in sustainability accounting. This paper contributes to understanding their barriers, using path dependence theory as a theoretical framework to empirically investigate how accountants have become “locked in” by self-reinforcing mechanisms. Based on semistructured interviews with 33 management accountants in Germany, the paper identifies three interrelated self-reinforcing mechanisms that inhibit accountants from sustainability involvement. A strong focus on financial priorities and incremental improvements driven by top management expectations hinder the consideration of sustainability beyond its direct costs. Specialization is another barrier, as is an understanding of sustainability as peripheral rather than a core business. Contrary to prior literature, accountants express eagerness to learn, though rarely about sustainability. They rarely question assumptions about sustainability and their role, leading to missed opportunities for double-loop learning and more transformative change.
Keywords: 650; corporate sustainability; management accounting practices; management control systems; path dependence theory; performance measurement; sustainability accounting